Scale-dependent effects of summer density on autumn mass in reindeer - Holand, Øystein; Ims, Anders Aa.; Weladji, Robert B. (Rangifer, 2010)
The ongoing dispute about reindeer overabundance in the West Finnmark (Norway) herding region has accentuated the need for an in-depth understanding of the density-dependent and -independent processes driving this pastoral system, as well as the spatial and temporal scale(s) they operate on. Using 20 604 records of individual male reindeer yearlings we assessed the spatial and temporal variation in animals’ performance (measured by their autumn carcass mass), and investigated summer density dependent effects on autumn carcass masses at different scales. We defined three spatial scales; a regional scale represented by the whole summer range of West Finnmark, a sub-regional scale represented by the mainland (14) and the island (11) summer districts, and a fine scale represented by eight individual summer districts. We defined two temporal scales; the whole collection phase (13 years) and a temporal dimension based on the three periods of population growth. We found carcass masses to be higher at island than at mainland and to vary among districts. Effect of period was found at the regional, sub-regional and often at the district scale. The autumn carcass masses were sensitive to density at West Finnmark and mainland scales, but not at island scale, the effect being negative. This suggests intra-specific competition for summer forage due to consistent higher density resulting in reduced range quality at mainland as compared to island. On the finest scale the density effect was highly variable. Response of carcass mass to density appeared to be scale dependent both in space and time at regional and sub-regional scales. These findings underline the importance, for skilful management, of site specific biological understanding of (1) the density dependent processes and (2) the spatial and temporal scales these processes are operating on. Adaptive management strategies for sustainable use of the summer forage resources in West Finnmark have therefore to be district specific. Skala-avhengige virkninger av antallet rein på høstslaktevektene i Vest-Finnmark Abstract in Norwegian / Sammendrag: Den stadig pågående diskusjon omkring reintall og overbelastning av beitene i Vest- Finnmark krever en bedre forståelse av tetthetsavhengige, så vel som tetthetsuavhengige prosesser som påvirker dette beitesystemet og på hvilke skalaer disse opererer. Vi benyttet 20 604 slaktevekter av varit (1,5 års gamle bukker) før brunst for å undersøke variasjonen i tid og rom i disse, og om sommerbeitebelegget på ulike skalaer påvirket vektene. Vi definerte tre romlig skalaer: 1) hele sommerbeiteområdet i Vest-Finnmark, 2) to underregioner: innlandsdistriktene samlet og øy/halvøydistriktene samlet og 3) det enkelte sommerbeitedistrikt. På distriktsnivå ble bare slaktedata fra 8 distrikt benyttet. Videre ble to tidsskalaer definert: 1) hele perioden samlet, 2) tre perioder basert på utviklingen i reintallet i Vest-Finnmark - økning i periode 1 (1983-87) og i periode 3 (2001-2004) og nedgang i periode 2 (1996 -2000). Slaktevektene var høyere for øy/halvøydistriktene sammenlignet med innlandsdistriktene samlet og varierte mellom distrikt. Periode påvirket også slaktevektene regionalt, subregionalt og ofte på distriktsnivå. Vi fant en negativ tetthetsavhengig effekt på slaktevektene for Vest-Finnmark samlet. Det samme gjaldt for innlandsdistriktene samlet, men ikke for øy/halvøydistriktene samlet. Dette forklares ved fødekonkurranse på innlandsdistriktenes sommerbeiter, sannsynligvis på grunn av at vedvarende høye tettheter har forringet beitekvaliteten, sammenlignet med øy/halvøydistriktene samlet. På distriktsnivå varierte effekten av tetthet. Resultatene tyder videre på skala-avhengige tetthetseffekter i tid og rom, i Vest-Finnmark samlet, så vel som på innlands- og øy/halvøynivå. Tetthet er et mangesidig og komplekst begrep som ikke kan sees uavhengig av skala. Det er derfor viktig å analysere slike prosesser på flere skalanivå for bedre å kunne forstå samspillet mellom vegetasjon og beitedyr. Dette innebærer i praksis at hvert sommerdistrikt (siida), som er den funksjonelle enheten i forvaltningssammenheng, må behandles uavhengig og danne grunnenheten i en fornuftig forvaltning.